CHIGLU: A Modular Hardware for Stepper Motorized Quadruped Robot—Design Approach and Analysis - Abid Shahriar; Monim Hasan Anik (MethodsX, 2025)
Bio-engineered robots are rapidly advancing due to the maneuverability they offer in navigating uneven terrains, driving advancement in electrical systems for robot control. This study presents a design approach, analysis, and fabrication of a compact Printed Circuit Board (PCB) as the carrier board, mounting low-cost motor drivers and a widely available microcontroller unit capable of controlling twelve stepper motors. The primary goal is to create a space-constrained, densely populated double-layer circuit board design yet an efficient hardware solution for stepper motorized quadruped robots. This research contributes significantly to stepper motor control systems for multi-axis applications in bio-inspired robots, offering a compact, reliable, and cost-effective hardware solution.Key methods include: • The development of a modular carrier board with swappable peripherals designed to meet power budget requirements and optimized through comprehensive design analysis • Conducting a PDN analysis for power distribution reliability and hardware testing.